2012
DOI: 10.3109/15513815.2011.650505
|View full text |Cite
|
Sign up to set email alerts
|

Liver Morphologic Analysis in Perinatal Autopsies with Intrauterine Stress Liver Morphology in Perinatal Autopsies

Abstract: Quantify steatosis, fibrosis, and focuses of extramedullary erythropoiesis (ER) in the liver and report it to the causes of death in the perinatal. Morphologic analysis of steatosis', percentage of fibrosis, and ER of 467 perinatal autopsies. Cases with hypoxia/perinatal anoxia and ascending infection showed higher percentage of fibrosis. The number of ER was significantly higher among premature infants and in cases with infection. Our results contribute to a better quality of perinatal care through clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This organ is enormously affected by intrauterine stress episodes, and morphological changes in this organ, such as steatosis, fibrosis, and foci of extramedullary erythropoiesis, are associated with perinatal death [6]. Altered hepatocytes change the pattern of CRP production, which in turn may serve as another marker of FIRS [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This organ is enormously affected by intrauterine stress episodes, and morphological changes in this organ, such as steatosis, fibrosis, and foci of extramedullary erythropoiesis, are associated with perinatal death [6]. Altered hepatocytes change the pattern of CRP production, which in turn may serve as another marker of FIRS [7].…”
Section: Introductionmentioning
confidence: 99%
“…One study evaluating infants who went through different kinds of stresses, such as intrauterine anoxia, infections, and congenital malformations, demonstrated that these children presented higher birth weight than the expected for the GA as well as a series of alterations in different organs, including the liver [6]. Possibly, the expression of the markers of FIRS in the liver of autopsied children might explain the increased weight gain and these markers may undergo variations according to the cause of death.…”
Section: Introductionmentioning
confidence: 99%
“…267 of the Ministry of Health of the Russian Federation (June 19, 2003). CAH was modeled by the placing of pregnant female rats (gestation days [14][15][16][17][18][19] into an altitude chamber and "ascent" to an altitude of 9000 m (pressure 224 mm Hg and oxygen saturation 42 mm Hg). Daily exposure lasted for 4 h. Parameters of liver tissue homeostasis in male offspring were measured on days 7 and 60 of postnatal development.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic antenatal hypoxia (CAH) induces mitochondrial dysfunction in the fetal liver cells in experimental animals [10]. Signifi cant changes including local steatosis, fi brosis, and erythropoiesis loci were found during liver autopsy in newborn children exposed to CAH [14]. Hepatocyte apoptosis develops during oxygen hypoxia-oxygenation [11].…”
mentioning
confidence: 99%